To solve the equation \( 2(x - 3) + 21 = -3 \), we can follow these steps:
Step 1: Distribute the \(2\)
Distribute \(2\) to both \(x\) and \(-3\):
\[ 2 \cdot x - 2 \cdot 3 + 21 = -3 \]
This simplifies to:
\[ 2x - 6 + 21 = -3 \]
Step 2: Combine like terms
Combine the constants \(-6\) and \(21\):
\[ 2x + 15 = -3 \]
Step 3: Isolate the term with \(x\)
Subtract \(15\) from both sides to isolate terms with \(x\):
\[ 2x + 15 - 15 = -3 - 15 \]
This simplifies to:
\[ 2x = -18 \]
Step 4: Solve for \(x\)
Divide both sides by \(2\):
\[ x = \frac{-18}{2} \]
This simplifies to:
\[ x = -9 \]
Solution
The solution to the equation \(2(x - 3) + 21 = -3\) is:
\[ \boxed{-9} \]